Mispronunciation of English Fricative Consonant Sounds by East Nusa Tenggara Students - Mada, Marianus Paulino (General English Education, 2025)
This study aims to examine the incorrect pronunciation of specific English fricative consonants (/v/, /θ/, /ð/, /ʃ/, /ʒ/) by Indonesian students, particularly those from East Nusa Tenggara who are studying English as a foreign language. Five male university students from East Nusa Tenggara province, who were brothers of the Society of the Divine Word and had attended an English course, were selected to study pronunciation of fricative consonants. The researchers conducted ten-word list, recorded the data, and analyzed the mistakes using the International Phonetic Alphabet (IPA). A native speaker assessed using a scoring rubric from 1-5. The pronunciation was correct if the scores were 4 and 5, while scores 1-3 were incorrect. The findings were then presented in the research. Results indicated typical substitutions of v/ with /f/, /θ/ with /t/, /ð/ with /d/, /ʃ/ with /s/, and /ʒ/ with /s. The study reveals that students in East Nusa Tenggara enhance their pronunciation and confidence by employing contextualized materials, foreign speakers, pronunciation software, audiovisual techniques, and community-based English activities.